Revisiting the Flaring Activity in Early 2015 of BL Lacertae Object S5 0716+714 - Zhihao Ouyang; Hubing Xiao; Marina Manganaro; Shangchun Xie; Jingyu Wu; Jianzhen Chen; Rui Xue; Gege Wang; Shaohua Zhang; Junhui Fan (The Astrophysical Journal)
In this work, we analyzed multiwavelength data of the BL Lac object S5 0716+714 to investigate its emission mechanisms during a flaring state observed in early 2015. We examined the temporal behavior and broadband spectral energy distributions (SEDs) during the flare. The size of the γ -ray emission region was estimated based on the variability timescale. To explore the multiwavelength properties of S5 0716+714, we employed three one-zone models: the synchrotron self-Compton (SSC) model, the SSC plus external Compton (EC) model, and the SSC plus pp interactions model, to reproduce the SEDs. Our findings indicate that, while the SSC model can describe the SEDs, it requires an extreme Doppler factor. In contrast, the SSC plus EC model successfully fits the SEDs under the assumption of weak external photon fields but requires a high Doppler factor. Additionally, the SSC plus pp interactions model also reproduces the SEDs, with γ -ray emission originating from π ^0 decay. However, this model leads to a jet power that exceeds the Eddington luminosity, which remains plausible due to the flaring state or the presence of a highly collimated jet.